In-vivo and in-vitro mutagenesis in marigold (Tagetes erecta) using 60Co gamma rays - SARKAR, JYOTI; SINGH, S K; SINGH, KANWAR PAL; GUHA, S K (The Indian Journal of Agricultural Sciences, 2016)
This study was conducted to induce novelty in marigold cultivar Pusa Narangi Gainda through gamma irradiation via in vivo and in vitro approaches. The seedlings grown under in vivo and the proliferated cultures under in vitro, were exposed to different doses of 60Co gamma rays (5, 10, 15, 20, 25, 30, 35, 40 Gy). 20 Gy and 15 Gy dose was identified as LD50 value for in vivo and in vitro conditions (53.24 % and 52.55 % plant survival), respectively. There were morphological variations in between irradiated and non irradiated plants. Treatment with 20 Gy induced early flower bud (49, 18 days) compared to control (55.56 days) under in vivo study. Under in vitro condition, the flower color changed to yellow (yellow 10 YR) compared to the control (orange 5 YR) at 15 Gy. In M1 generation, two mutants in flower form (m1 and m3), one in colour (m4) and another one in flower earliness (m2) were isolated under in vivo mutation, whereas, five mutants in flower colour (nm1, nm2, nm5, nm6 and nm7) and two in flower form (nm3 and nm4) were isolated in irradiated plants which were quite distinct compared to non-irradiated. Variability caused by induced mutations need not to be essentially different from variability caused by spontaneous mutation during evolution, therefore, it is necessary to carry on the M2 generation. The mutants which were selected from the M1 generation were selfed to raise the M2 generation. The study revealed six putative mutants (pm1, pm2, pm3, pm4, pm5 and pm6), which could successfully maintain their distinct traits. Among them, pm3 produced early flowering in 47.89 days and pm4 gave light orange coloured flower (orange 10 YR).